(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to study the requirements for applying electronic automation in the General Tax Authority, as it included a study of its dimensions (regulatory requirements, technical requirements, human requirements) to reveal the extent of the possibility of applying electronic automation in the General Tax Authority through (regulatory requirements, technical requirements, human requirements). The research adopted a theoretical framework that explains the concept, importance, objectives, advantages, disadvantages, application requirements and application determinants. To achieve the goal of the research, the method of analyzing data and information obtained by the researcher from conducting interviews with a number of department managers in the General Tax Authority and some lists of inventory of the number of employees and annual inventory lists of assets for the departments in the research sample from the Authority’s departments (Companies Department, Large Taxpayers Department, Electronic Calculator Department). The researcher reached a set of conclusions, the most important of which is the lack of financial allocations in the general budget for 2022 and 2023 for the General Tax Authority. The Authority relies on the intranet as an internal network, and there is a lack of specialized staff in the field of automation in the companies’ department and the senior taxpayers department. The researcher recommended that the tax administration develop the necessary plans to implement electronic automation and provide the necessary and effective material capabilities and financial appropriations to implement automation and hold training courses for estimators in the field of electronic automation and pay attention to protecting the security system from hacking and viruses to protect the privacy of electronic information.